2012
DOI: 10.1021/jp206798d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BiVO4 Crystalline Phases on the Photoinduced Carriers Behavior and Photocatalytic Activity

Abstract: A series of different crystalline phases BiVO 4 photocatalysts (tetragonal, monoclinic, and monoclinic/tetragonal heterophase) have been prepared by a coprecipitation and molten salt method. High-resolution transmission electron microscopy (HRTEM) results show that an interface of intimate contact is formed in monoclinic/tetragonal heterophase and monoclinic phase is mainly on the surface of nanoparticles. Surface photovoltage (SPV) and transient photovoltage (TPV) techniques are used to further investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(128 citation statements)
references
References 28 publications
3
123
0
2
Order By: Relevance
“…25 These results clearly show that the behaviour of photoinduced charges is markedly dependent on the BiVO 4 crystalline phases. Moreover, the presence of an interface in the monoclinic/tetragonal heterophase provides a spatial condition for charge transfer.…”
Section: Introductionmentioning
confidence: 68%
“…25 These results clearly show that the behaviour of photoinduced charges is markedly dependent on the BiVO 4 crystalline phases. Moreover, the presence of an interface in the monoclinic/tetragonal heterophase provides a spatial condition for charge transfer.…”
Section: Introductionmentioning
confidence: 68%
“…Thus, Fan et al reported that the particular m-t heterostructured BiVO 4 is expected to promote the separation of photoinduced electron-hole pairs. 24,25 In spite of this, the exalted performance of Er-doped t-BiVO 4 (6.0 × 10 −4 s −1 ) with respect to the t-BiVO 4 (3.0 × 10 −4 s −1 ) system cannot be attributed only to a surface area contribution or the presence of a small amount of monoclinic phase. Indeed, much research has shown that the surface area would play a key role in the final photocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…28 The improved photocatalytic performance of m-t heterostructured BiVO 4 has been associated to promotion photoinduced electron-hole pairs separation. 29 Within this framework, Obregón et al reported the unexpected enhanced photocatalytic activity of tetragonal stabilized Ln-doped BiVO 4 . 30,31 Moreover, by changing the precursor addition sequence in the synthesis route, we have obtained a monoclinic-tetragonal heterostructured Er 3+ -BiVO 4 exhibiting notably a high photoactivity under sun-like irradiation.…”
Section: 16mentioning
confidence: 99%